Examining Differentiating Characteristics of Individuals Who Cross Over Into The Criminal Justice System In Relation To Their Substance Abuse Treatment - Compani, Leyla (2017)
INTRODUCTION: In Georgia, criminal justice (CJ) involvement is one of the costliest outcomes experienced by individuals with substance abuse problems. Approximately 8% of individuals in America have needed substance abuse treatment, and in Georgia CJ involvement commonly co-occurs. AIM: To examine the transition into the CJ system for those entering treatment, and, arrests of individuals in treatment. The aim is to determine defining characteristics exist for an individual who switches over into the CJ system, or an individual who has an arrest while in treatment. METHODS: Data from the Treatment Episode Data Set from 2011-2015 was examined. Demographics, drug types, frequency of use, poly drug use, number of treatment episodes, time between treatment episodes, and rural and urban geography are analyzed in relation to the dependent study variables. Analytic techniques used are independent samples t-tests and regression analyses. The dependent variables are any switchover into the criminal justice system upon reentering treatment, and any arrest before discharge from treatment. RESULTS: Factors associated with a switch into the CJ system upon admission are non-completion of high school, ever being unemployed or a student (18 yrs or older), poly drug use, more than one treatment episode, younger at age of first drug use, longer periods of time in treatment, a switch of primary drug to meth, crack-cocaine, opiates, marijuana, or alcohol. Attending self-help programs before entering treatment and living in rural areas also increases a switch to the CJ system. Higher risk of arrest is associated with younger at age of first drug use, being male, black or other non-white race, higher education levels, ever being a student or homeless, attending self-help programs, and living in urban areas. DISCUSSION: The results and interpretation of this study may help inform and direct one part of a criminal justice prevention strategy and evidence-based health policy, for individuals who are undergoing substance abuse treatment